Embodied Technologies: Integration and Orchestration in Authentic Classroom Contexts - Ioannou, Marianna (My University, 2023)
A new generation of technologies that harness the affordances of motion is gaining the attention of the educational community due to evidence that they can enhance student engagement and embodied learning. However, integrating these embodied learning technologies in classroom contexts requires appropriate pedagogical strategies and guidelines, which are not yet well-defined. This dissertation addresses this gap by exploring the integration and orchestration of embodied learning technologies in authentic classroom contexts. It documents orchestration strategies and guidelines for successful integration, based on evidence drawn from four cycles of design-based research (DBR). The first DBR cycle investigated the main challenges of introducing technology-enhanced embodied learning in a classroom context and how the experience was perceived by the learners. The second DBR cycle sought to understand what pedagogical elements might be considered for establishing meaningful integration of embodied learning technology around complete lessons. It also extended our understanding of students’ perceptions of the learning experience in high-embodied vs low-embodied technology-enhanced embodied learning conditions. In the third DBR cycle, we applied initial principles for orchestrating technology-enhanced embodied learning in the classroom. We designed a classroom experience for embodied learning in learning stations with students rotating on a fixed schedule, using high-embodied technologies along with more conventional paper-and-pencil tools. At the end of this cycle, newly generated design principles for real-world classroom settings were documented. In the fourth and last cycle of work, we aimed to replicate and confirm the orchestration strategy derived from the previous cycle and we revisited learning aspects in technology-enhanced embodied learning which were unclear in earlier cycles of the work. The dissertation concludes with practical guidelines and implications for educators and researchers who wish to incorporate embodied learning technologies in their curricula toward an engaging learning experience in real-world classrooms.
Keywords: embodied technologies; technology-enhanced embodied learning; technology integration; classroom orchestration